2016
DOI: 10.1021/acs.energyfuels.5b02614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Strength on the Interfacial Forces between Oil/Brine/Rock Interfaces: A Chemical Force Microscopy Study

Abstract: The presence of thin aqueous films and their stability have a profound effect on the interactions between oil/brine/rock interfaces. In a previous report, we proposed that hydration forces, originating from the overlap of hydrated layers of different surfaces in the presence of sodium chloride, played an important role at short range. In the present work, divalent ions were introduced to the liquid films and, the mechanisms in improving oil recovery from low-salinity brine and the low-salinity effect at the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…However, all above mentioned studies have been carried out from core-scale to reservoir-scale. While the atomic force microscopy (AFM) [28,29] and quartz crystal microbalance with dissipation (QCM-D) [30] were used to investigate the effect of water chemistry on adhesion force, few have investigated correlation of nano-scale mechanism(s) of wettability alternation and core-scale experimental results, and fewer have looked beyond the simple and practical approach to guide industry to engineer the injected water chemistry, thus improving oil recovery based on disturbing the in-situ thermodynamic equilibrium. Our objectives were to gain better understanding of low salinity water flooding in nano-scale by addressing the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…However, all above mentioned studies have been carried out from core-scale to reservoir-scale. While the atomic force microscopy (AFM) [28,29] and quartz crystal microbalance with dissipation (QCM-D) [30] were used to investigate the effect of water chemistry on adhesion force, few have investigated correlation of nano-scale mechanism(s) of wettability alternation and core-scale experimental results, and fewer have looked beyond the simple and practical approach to guide industry to engineer the injected water chemistry, thus improving oil recovery based on disturbing the in-situ thermodynamic equilibrium. Our objectives were to gain better understanding of low salinity water flooding in nano-scale by addressing the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, our data can be compared with previous CFM studies of the adsorption of other functionalities at the aqueous electrolyte/model sandstone interface. The adhesion of an alkyl-terminated tip at the aqueous electrolyte/mica interface was dependent on both NaCl and CaCl 2 concentration 19 . A low-salinity response was also observed for a COOH/COO − functionalized tip at an amorphous silica surface in artificial seawater: at high salinity (36,500 ppm), adhesion was 46 pN compared with 33 pN at low salinity (1400 ppm) 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The chemical force mapping mode (CFM) of atomic force microscopy (AFM) can be used to determine adhesion force. CFM experiments showed that the adhesion of an alkyl-terminated tip to mica was ~23× stronger in aqueous CaCl 2 than in aqueous NaCl at three different concentrations (10 mM, 100 mM and 1000 mM) 19 . In contrast to previous studies 16 , 17 , the adhesion depended on the concentration of NaCl.…”
Section: Introductionmentioning
confidence: 98%
“…In the present paper, DLVO theory was extended to provide a more complete interpretation of force-distance experimental data, as expressed in eqn 7: 38,46,47…”
Section: Extended Dlvo Modelmentioning
confidence: 99%